Linear predictor and autocorrelation for noisy and delayed digital signal - G Vinu Priya; R Jothilakshmi (Ratio Mathematica, 2023)
This paper deals with the association between the linear prediction and digital signal modeling and ends up with the suitable ways to predict the signal by considering a stationary signal $y_{n}$. The linear prediction of signal modeling based on the finite past and the solutions are arrived in a recursive manner. Further we analyzed the wiener filter along with spectral theorem and autocorrelation in terms ofpredictive analysis.This estimates the gap function along with delay and noise. The delayed signal’sproperties are analyzed like causal, stability and applied these into optimum filtering. Finally the predicted error is compared with linear predictor and Wiener filter. Then transfer function is applied to estimate the interval function and gap function along with delay.